The Influence of Product Quality, Brand Image and Price on the Decision to Purchase a Mitsubishi L-300 Pick Up PT Car. Pekanbaru Pahala Automotive International Dipo - Maharani, Maharani; Musfar, Tengku Firli; Alvionita, Agnes (CV. Rayyan Dwi Bharata, 2025)
This research aims to examine the influence of product quality, brand image, and price on the purchase decision of the Mitsubishi L-300 Pick Up at PT. Dipo Internasional Pahala Otomotif. The type of research used is quantitative research. The population in this study consists of 3,498 buyers of the Mitsubishi L-300 Pick Up from PT. Dipo Internasional Pahala Otomotif. The sample for this study was determined using the Slovin formula, resulting in 96 respondents. The research uses Mitsubishi L-300 Pick Up buyers as the object of the study. The sampling method follows Slovin's formula, resulting in 97 respondents. Data analysis methods include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and the coefficient of determination, with a significance level of 0.05. The data analysis was performed using SPSS version 23 software. The results indicate that, partially, product quality has an influence on purchase decisions. There is no significant influence of brand image on purchase decisions. However, price and purchase decisions are influenced simultaneously by product quality, brand image, and price.